2019
DOI: 10.1111/cpr.12631
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 11 inhibits adipogenic differentiation by activating TGF‐beta/Smad signalling pathway

Abstract: Objectives Growth differentiation factor 11 (GDF11), an emerging secreted member of the TGF‐beta superfamily, plays essential roles in development, physiology and multiple diseases; however, its role during adipogenic differentiation and the underlying mechanisms remains poorly understood. Materials and methods Bone marrow‐derived human mesenchymal stem cells (hMSCs) and 3T3‐L1 pre‐adipocytes were induced with adipogenic culture medium supplementing with different conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…Little research has been performed on GDF11, but a recent article discussed the effect of GDF11 on adipocyte commitment. The data indicated that GDF11 inhibited adipogenic differentiation in human MSCs by activating SMAD2/3-dependent TGF-β signaling [75]. It is becoming clear that R-SMADs have an impact on the commitment of MSCs, but we still know very little about Co-SMAD (SMAD4).…”
Section: Resultsmentioning
confidence: 99%
“…Little research has been performed on GDF11, but a recent article discussed the effect of GDF11 on adipocyte commitment. The data indicated that GDF11 inhibited adipogenic differentiation in human MSCs by activating SMAD2/3-dependent TGF-β signaling [75]. It is becoming clear that R-SMADs have an impact on the commitment of MSCs, but we still know very little about Co-SMAD (SMAD4).…”
Section: Resultsmentioning
confidence: 99%
“…Transforming Growth Factor-β (TGF-β) family ligands, which include TGF-β, Activin, GDF, and BMP family growth factors, have known roles in both adipogenesis and adipocyte hypertrophy (Lee, 2018, Tang & Lane, 2012, Zamani & Brown, 2011. Thus, TGF-β1, GDF-8, and Activins A and B inhibit adipogenesis (Choy, Skillington et al, 2000, Hirai, Yamanaka et al, 2005, Hoggard, Cruickshank et al, 2009, Ignotz & Massague, 1985, Kim, Liang et al, 2001, Lee, Pickering et al, 2019, Luo, Guo et al, 2019, Sparks, Allen et al, 1992, whereas several BMPs have been shown to promote adipogenesis and/or adipocyte hypertrophy (Gustafson, Hammarstedt et al, 2015, Huang, Song et al, 2009, Modica & Wolfrum, 2017, Schreiber, Dorpholz et al, 2017, Tang, Otto et al, 2004, Tseng, Kokkotou et al, 2008. Yet in spite of a large body of work in this area, fundamental questions remain unresolved, including what steps of adipogenesis are regulated by specific TGF-β family pathways, how are intracellular signaling pathways activated to direct adipocyte development, and can extracellular TGF-β family inhibitors help control adipogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Selecting the appropriate signaling pathway downstream of RARγ is very important. The Smad2/3 signaling pathway has recently been shown to be central to the regulation of adipogenesis [ 55 57 ]. In addition, this signaling pathway involved in non-coding RNA has also been shown to play an essential role in the context of cancers, cell differentiation, and migration [ 58 60 ].…”
Section: Discussionmentioning
confidence: 99%